Mobbing causes, consequences, and solutions - Duffy, Maureen P.; Sperry, Len. (New York ; Oxford : Oxford University Press, 2012)
This work addresses the devastating impact that mobbing has on victims, their families, and the organizations in which it occurs. The book provides a fascinating analysis of how organizations can foster mobbing, and what can be done to help mobbing victims and their organizations to heal.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Bullying; Harassment; Intimidation; Organizational behavior